The structure of ground reaction force in vertical counter movement jump at different intensities - Vaverka, F.; Gajda, V. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of the study was to ascertain the structure of ground reaction force CMJ (counter movement jump) at varying intensity of take-off, and further, to evaluate the mechanisms of performing final force impulse. CMJ, in three intensive varieties comprising maximal intensity, 75% intensity and 50% intensity, was conducted in a group of 44 university students. The vertical component of reaction force F(t) was analyzed in terms of force, time and track take-off parameters. Statistical analysis confirmed differences between take-offs at different intensities in the magnitude of force impulse, track and time variables of the F(t) curve. The crucial factor influencing the creation of force impulse is the range of the CG track in the preparation and acceleration phases.